Carbon dots derived from cellobiose for temperature and phosalone detection. (July 2022) - Liao, Xiufen; Chen, Congjin; Wang, Peiwen; Zhou, Ruxia; Zhao, Xilian; Fan, Hui; Huang, Zuqiang
Highlights: The formation of the cellobiose-derived CDs was discussed in detail. N atoms as the "molecular glue" to improve the quantum and generation yield of CDs. The temperature sensor based on the dual fluorescence centers of the N-CDs was constructed Dual ratiometric modes for phosalone analysis was proposed via the as-prepared N-CDs. Abstract: Cellobiose, the hydrolysis product of cellulose and the dimer of glucose, was employed to synthesize carbon dots (CDs) via a simple hydrothermal method. The inducing of nitrogen can act as a "molecular glue", more and more carbon clusters were "glued" together, which would push the hydrothermal reaction in the positive direction. Besides, the linear response of the fluorescence of N-CDs to temperature ensured its potential application in temperature sensing. In the temperature range of 10∼80 °C, the fluorescence of as-prepared N-CDs was reversible and recoverable. Moreover, the dual fluorescence centers and dual-absorption bands of the as-prepared N-CDs permitted the novel dual-mode ratiometric assays for phosalone detection. The linear range and limit of detection (LOD) for dual fluorescence center-based ratiometric assay were 0.12∼5.45 μg/mL and 42.90 ng/mL, respectively. While that for the dual absorption-based ratiometric assay were 0.02∼1.40 μg/mL, and 6.67 ng/mL, respectively. Graphical abstract: In this paper, cellobiose was employed to synthesize carbon dots via a facile hydrothermal method. The formation mechanism of CDs was discussed in detail. Image, graphical abstract